Respuesta :
Answer: plse use the given formula in rs aggarwal book
Step-by-step explanation:
To prove by mathematical induction, let Pₙ be the equation:
Let Pₙ be 4 +9 +14 +...+(5n -1)= (n/2)(5n +3).
1) Base step: prove P₁ is true
When n=1,
LHS= 4
RHS
[tex] = \frac{1}{2} (5 + 3)[/tex]
[tex] = \frac{1}{2} (8)[/tex]
= 4
= LHS
∴ P₁ is true.
2) Assume Pₙ is true,
i.e. 4 +9 +14 +...+(5n -1)= (n/2)(5n +3)
3) Induction step: prove Pₙ₊₁ is true
Find Pₙ₊₁ by substituting (n+1) into n on both sides.
Pₙ₊₁: 4 +9 +14 +...+(5n -1)+ [5(n+1) -1]=
[tex]( \frac{n + 1}{2} )[5(n + 1) + 3][/tex]
Prove that the LHS is equal to the RHS.
LHS
= 4 +9 +14 +...+(5n -1)+ [5n +5-1]
[tex]= \bf{4 +9 +14 +...+(5n -1)}+ (5n +4)[/tex]
Substitute the value of Pₙ in (2) into bolded expression:
[tex] = \frac{n}{2} (5n + 3) + 5n + 4[/tex]
[tex] = \frac{5}{2} n^{2} + \frac{3}{2}n + 5n + 4 [/tex]
[tex] = \frac{1}{2} (5 {n}^{2} + 3n + 10n + 8)[/tex]
[tex] = \frac{1}{2} (5 {n}^{2} + 13n+ 8)[/tex]
[tex] = \frac{1}{2} (n + 1)(5n + 8)[/tex]
[tex] = \frac{n + 1}{2} (5n + 8)[/tex]
[tex] = \frac{n + 1}{2} [5(n + 1) + 3][/tex]
= RHS
(shown)
4) Write concluding statements
∴ If Pₙ is true, Pₙ₊₁ is true
Since P₁ is true, Pₙ is true for all positive integers of n.
To learn more about mathematical induction, do check out the following!
- https://brainly.com/question/24393371